2012
DOI: 10.5194/bg-9-5181-2012
|View full text |Cite
|
Sign up to set email alerts
|

Density fractions versus size separates: does physical fractionation isolate functional soil compartments?

Abstract: Abstract. Physical fractionation is a widely used methodology to study soil organic matter (SOM) dynamics, but concerns have been raised that the available fractionation methods do not well describe functional SOM pools. In this study we explore whether physical fractionation techniques isolate soil compartments in a meaningful and functionally relevant way for the investigation of litter-derived nitrogen dynamics at the decadal timescale. We do so by performing aggregate density fractionation (ADF) and partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 75 publications
2
42
1
1
Order By: Relevance
“…7a and b). The limited effects of OM occlusion in aggregates are not consistent with the general view of aggregate-controlled OM stabilization (Lehmann and Kleber, 2015;Wiesmeier et al, 2019), as well as other studies revealing aggregate-protected OM using similar aggregate destruction methods (Mueller et al, 2012;Wang et al, 2014). However, Goebel et al (2009) and Juarez et al (2013) reported limited roles of soil aggregates in protecting OM from decomposition.…”
Section: Organic Matter Stabilization Mechanismscontrasting
confidence: 57%
See 1 more Smart Citation
“…7a and b). The limited effects of OM occlusion in aggregates are not consistent with the general view of aggregate-controlled OM stabilization (Lehmann and Kleber, 2015;Wiesmeier et al, 2019), as well as other studies revealing aggregate-protected OM using similar aggregate destruction methods (Mueller et al, 2012;Wang et al, 2014). However, Goebel et al (2009) and Juarez et al (2013) reported limited roles of soil aggregates in protecting OM from decomposition.…”
Section: Organic Matter Stabilization Mechanismscontrasting
confidence: 57%
“…(1) OM adsorption on the mineral surfaces and (2) physical occlusion of OM within soil water-stable aggregates (Lützow et al, 2006;Six et al, 2002). In general, OM occluded in water-stable aggregates is isolated using wet-sieving followed by density fractionation plus sonication (Cerli et al, 2012;Moni et al, 2012). However, these methods were not applicable for our acid igneous rock soils because the application of ultrasound caused severe dispersion of OM into the dense solution (i.e., NaPT).…”
Section: Organic Matter Stabilization Mechanismsmentioning
confidence: 99%
“…Although we observed large impacts of grazing on BCA and SOC pools, future work will be needed to gain greater mechanistic insight into the processes regulating SOC turnover, and thus long-term implications of grazing for carbon sequestration. For instance, our findings support that plant tissue inputs account for a disproportionate fraction of SOC under grazing, but we do not have data to link this pattern to any particular fraction of SOC (von L€ utzow et al, 2007;Moni, Derrien, Hatton, Zeller, & Kleber, 2012). We speculate that it is possible that particulate forms of SOC are promoted by grazing, while the absolute concentration of mineral-associated C is similar due to saturation of physical-protection capacity in coarse sandy soils.…”
Section: Discussionmentioning
confidence: 60%
“…Conceptual pools were sometimes associated to functional pools tentatively separated from soils according to chemical or physical fractionation (e.g. Balesdent 1996;Zimmermann et al 2007;Crow et al 2007;Moni et al 2012). In recent years, the significance of the chemical fractions obtained after the so-called humic substances separation have been questioned since they are probably artefacts formed during the drastic chemical extraction treatment (Schmidt et al 2011).…”
Section: Introductionmentioning
confidence: 99%